Determination of Candidates for Madrasah Aliyah Student Scholarships Using The Simple Additive Weighting Method - Herdiansah, Arief (Universitas Trilogi, 2023)
Scholarships are a facility expected by some students who need financial assistance in their education. Case study research at MAN 3 Tangerang as a state Islamic senior high school, MAN 3 Tangerang has facilities to propose students who have achievements and need educational funding assistance to the Indonesian Ministry of Religion (Kemenag). Schools often find it difficult to determine which prospective students are most eligible for scholarships. This research is to help the school design and develop a decision support system (DSS) application with the Simple Additive Weighting (SAW) method. DSS application built using UML design and PHP (Hypertext Processor File) programming with MySQL database. The resulting DSS application has been able to provide a sequence of data for prospective scholarship recipients according to the criteria and weightings that have been set. Based on the data generated by the system, the principal can make a decision on who is entitled to a scholarship from the Ministry of Religion (Kemenag).